2016
DOI: 10.1515/eletel-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Fast Selection of Intraframe Prediction Mode in HEVC

Abstract: In the new HEVC standard, there are 35 intraframe prediction modes. Therefore, real-time implementations need fast mode pre-selection to reduce the computational load of cost comparison for individual modes. In this paper, a simple technique is proposed to reduce the complexity of the Unified Intra Prediction by decreasing the mode candidate number evaluated in the Rough Mode Decision step. We call this approach hierarchical as we decrease stepwise the angles between the directions of the prediction modes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…It also makes use of the correlation between the rough mode and the most promising mode decision. Jakub Siast et al (2016) [3] demonstrated a hierarchical technique where the subsets of every second, third and fourth modes are created and the most probable modes are checked against those subsets. The method checks for near optimal RD costs and reduces the time for Rough mode decision.…”
Section: Fig 1: Reference Array For Hevc Intrapredictionmentioning
confidence: 99%
“…It also makes use of the correlation between the rough mode and the most promising mode decision. Jakub Siast et al (2016) [3] demonstrated a hierarchical technique where the subsets of every second, third and fourth modes are created and the most probable modes are checked against those subsets. The method checks for near optimal RD costs and reduces the time for Rough mode decision.…”
Section: Fig 1: Reference Array For Hevc Intrapredictionmentioning
confidence: 99%
“…Meanwhile, according to the RD cost of the neighboring CUs, early termination methods are proposed to decide the prediction modes and CU sizes. In [9], the hierarchical fast mode selection is proposed by restraining the search scope of intra prediction modes. The RD cost of each prediction mode indicates the gradient in the block.…”
Section: Introductionmentioning
confidence: 99%